Generative Propagation of Teak (Tectona grandis. Linn. F sp.) Using Seeding Method - Yagoub, Salih Soood (Nabatia, 2024)
In the Diyla area, fourteen ground water samples were obtained for this study in high density polyethylene (HDPE) bottles that had been previously cleaned and filled with diluted HNO3. To prevent cross-contamination, the bottles were rinsed with the same water that would be used for the sample. Using normal procedures, each sample was examined for five parameters: TDS, Ca, Mg, No3, So4, and F (APHA, 1995). Using the Trimble Juno 3D Handheld, the sampling sites' geographic locations are gathered. Electrical Conductivity (EC) was used to compute Total Dissolved Solids (TDS). Spectronics 21 (Model BAUSCH AND LOMB) was used to measure nitrates (NO3-) and sulphates (SO4-2). Standard AgNO3 was used to estimate chloride (Cl-), and an Orion ion analyzer with an ion-selective electrode was used to analyse fluoride (F-). With the exception of pH and EC, all the parameters are presented in mg/l. The unit of EC expression is micro Siemens/cm.